Pharmacokinetic and Pharmacodynamic Modeling and Simulation Analysis of CTB-001, a Recently Developed Generic of Bivalirudin - Han, Sungpil; Kim, Yo-Han; Choi, Hee Youn; Kim, Mi-Jo; Kim, Wan Joo; Park, Hyunjung; Bae, Kyun-Seop; Lim, Hyeong-Seok (Pharmaceutical research, 2019)
Purpose CTB-001, a recently developed generic version of bivalirudin, an FDA-approved anticoagulant used for prophylaxis and treatment of cardiovascular diseases, has shown good efficacy and safety in clinical trials. We characterized the pharmacokinetics (PK) and pharmacodynamics (PD) of CTB-001 by modeling and simulation analysis. Methods PK/PD data were collected from a randomized, double-blind, placebo-controlled, single-dose, dose-escalation phase 1 study conducted in 24 healthy Korean male subjects. PK/PD analysis was conducted sequentially by nonlinear mixed-effects modeling implemented in NONMEM®. Monte-Carlo simulations were conducted for PK, activated partial thromboplastin time (aPTT), prothrombin time (PT), and thrombin time (TT). Results The CTB-101 PK was best described by a three-compartment linear model with a saturable binding peripheral compartment. All PD endpoints showed dose-response relationship, and their changes over time paralleled those of CTB-101 concentrations. A simple maximum effect model best described the aPTT, PT in INR, PT in seconds, and TT, whereas an inhibitory simple maximum effect model best described PT in percentages. The maximum duration of effect of CTB-001 on aPTT prolongation was 52.1 s. Conclusions The modeling and simulation analysis well-characterized the PK and PD of CTB-001 in healthy Koreans, which will be valuable for identifying optimal dosing regimens of CBT-001.